Specificity: A Phenotypic Comparison of Communication-Relevant Domains Between Youth With Down Syndrome and Fragile X Syndrome - del Hoyo Soriano, Laura; Thurman, Angela John; Abbeduto, Leonard (Frontiers in Genetics, 2018)
Despite the shared presence of an intellectual disability (ID), there is a growing literature documenting important phenotypic differences between Down syndrome (DS) and fragile X syndrome (FXS). These conclusions, however, are based on a synthesis across studies, each of which typically includes only measures of a limited number of constructs, and with differing participant characteristics. Firmer conclusions regarding specific phenotypes require a single comprehensive multi-domain assessment of participants with the syndrome groups being well matched on chronological age (CA) and cognitive functioning. The current study was designed to fill this gap by assessing several important cognitive and behavioral domains relevant to communication, such as: structural language skills, false belief understanding, as well as pragmatics and behavioral difficulties, in 30 adolescents of both sexes with DS and 39 males with FXS, matched on CA and nonverbal (NV) cognition. After statistically controlling for NV cognition, we did not find significant syndrome differences in expressive and receptive structural language or false belief understanding. In contrast, participants with DS displayed less stereotyped language and fewer behavioral difficulties compared to males with FXS. Within-syndrome associations among the targeted domains are described. Finally, females with DS were less impaired than males with DS in almost all structural language domains, whereas no significant sex-related differences were observed in NV cognition, false belief understanding, pragmatics, or behavior. Clinical and methodological implications of the findings are discussed.